Fast evolutionary response of house mice to anthropogenic disturbance on a Sub‐Antarctic island. (14th January 2015) - Renaud, Sabrina; Gomes Rodrigues, Helder; Ledevin, Ronan; Pisanu, Benoît; Chapuis, Jean‐Louis; Hardouin, Emilie A.
<x xml:space="preserve">Abstract</x> Invasions and anthropogenic disturbances challenge species with rapid environmental changes. Understanding how organisms respond to these changes is of major concern for the future of biodiversity. The house mouse on a Sub‐Antarctic island (Guillou Island, Kerguelen Archipelago) had to face such challenges twice: first when invading the island two centuries ago; and nowadays when coping with an in‐depth remodeling of its habitat due to a cohort of anthropogenic changes. Morphometric and biomechanical results show that the initial invasion triggered the evolution of a jaw shape adapted to the local food resources. Contemporary changes are also associated to changes in jaw morphology, but are not directly functionally relevant. Here, a complex response integrating feeding behaviour, investment in feeding structure, and degree of mineralization, may provide the mice with a better tool to benefit of wider resources utilization and/or better cope with intra‐specific competition in a changing habitat. These Sub‐Antarctic mice exemplify that success of invasive species rely on the capacity of facing rapidly varying environments through integrated, multi‐faceted responses involving behaviour to morphology through life‐history traits. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 513–526.